An immunological overview of allergen specific immunotherapy — subcutaneous and sublingual routes - (:unkn) unknown (My University, 2009)
Allergen-specific immunotherapy remains the most likely effective treatment modality for allergic disorders by targeting the underlying immune mechanisms and possibly causing modifications in the disease course, as well as treating the symptoms. Treatment and compliance experiences been gained over nearly a century in injection-type allergen-specific immunotherapy have motivated the development of newer, alternative routes. Adverse events and safety concerns, efficacy and ease of application seem to be the stimulating factors for the development of a sublingual form of this treatment modality, wherein the principal factor is the capture of the antigen (allergen) by dendritic cells, in the location where oral tolerance arises. Due to the presence of high numbers of tolerogenic dendritic cell subsets in this region, programming of the immune system towards a regulatory state with unresponsiveness to specific allergens occurs. Induction of peripheral tolerance through the generation of regulatory T cells is the key event, with several functional modulations in the allergic immune response. With an increase in understanding of the mechanism of regulatory pathways, promising progresses in the field of allergen-specific immunotherapy will ensue and may provide new options for the treatment of allergic disorders. © 2009, SAGE Publications. All rights reserved.
Keywords: allergy; asthma; atopy; regulatory T cell sublingual immunotherapy; subcutaneous immunotherapy